A novel cage-like CdTe film with enhanced photoelectrochemical performance. Issue 49 (3rd May 2016) - Wang, Jun; Lv, Pin; Mu, Yannan; Ding, Dong; Liu, Li; A, Runa; Feng, Fei; Feng, Shuang; Fu, Wuyou; Yang, Haibin
Abstract : A novel cage-like CdTe film with even porosity size and good connectivity among particles is successfully prepared by a simple technique for the first time. Abstract : A novel cage-like CdTe film with even porosity size and good connectivity among particles is successfully prepared by a simple technique for the first time. The field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and UV-Vis absorption spectra are used to characterize the morphology, crystallinity and optical property of the new structure. The FESEM observation confirms the formation of cage-like CdTe film after heat treatment. The structural and optical studies reveal that the cage-like CdTe films show better crystallinity and enhanced optical absorption. Based on the characterization results, the possible growth mechanism of the cage-like CdTe film is proposed. Furthermore, the photoelectrochemical property of the film is also investigated by photocurrent and current density–voltage curves and electrochemical impedance spectroscopy (EIS). The cage-like CdTe film yields an enhanced photocurrent and current density of 3.8 mA cm −2, which is significantly higher than other as-prepared CdTe films. Meanwhile, the cage-like CdTe films present improved charge transfer properties and corroborate the photocurrent and current density–voltage measurements. The photostability of the films is also studied. The better photoelectrochemical property of the cage-like CdTe films suggests their potential application in nanostructured solar energy conversion devices.